Formulation of escitalopram emulsion using a novel bio- emusifier from unriped fruit pulp of Artocarpus heterophyllus - N.V. Satheesh Madhav, Pranshu Tangri (Journal of Applied Pharmaceutical Science)
The aim of our research work was to isolate a novel bio-material from unripe fruit pulp of Artocaropus heterophyllus, and to evaluate its bio-emulsifying ability by formulating escitalopram emulsions. The bio-material was isolated from the unripe fruit pulp of Artocarpus heterophyllus by simplified economic process. It was subjected for various physicochemical parameters like color, colour changing point, chemical tests, IR spectral study. Four Drug loaded emulsions were formulated(AH1-AH4) using varying ratios of the bio-material. The emulsions were formulated using Escitalopram as a model drug. The formulated emulsions were subjected for evaluation parameters like globule size, pH, effect of centrifugation, viscosity, surface tension, creaming, freezing and thawing cycles and in-vitro release. The infra red spectra of the bio-material showed the presence of saturated hydrocarbons, aromatic ring and secondary and tertiary alcohol groups. The emulsions showed a globule size in the range 0.15-0.17µm, viscosity of 11.4±0.5cp to 17.6±1.2cp, surface tension in the range 59.67±1.3 to 65.42±1.45 dyne/cm. The emulsions had content uniformity of 73%±2.1% to 81%±1.85%. The in-vitro drug release studies from the formulated emulsions exhibited a controlled release for a period of 8 hours. The formulation AH3 was found to be best formulation on the basis of evaluation parameters, in-vitro release study and stability study. It showed content uniformity of 77% and was found to be stable with no signs of phase separation, creaming and showed controlled release of more than 8 hours with t80% of more than 5.5 hours. The emulsions followed zero order release as shown by the higuchi model. The release curves were fitted to korsenmeyer equation and showed linear release profile.
Keywords: Artocaropus heterophyllus, Escitalopram, emulsions, bio-material